Immune Reconstitution-Based Score for Risk Stratification of Chronic Graft-Versus-Host Disease Patients - Fabio Serpenti; Francesca Lorentino; Francesca Lorentino; Sarah Marktel; Raffaella Milani; Carlo Messina; Raffaella Greco; Stefania Girlanda; Daniela Clerici; Fabio Giglio; Carmine Liberatore; Francesca Farina; et al. (Frontiers in Oncology, 2021)
IntroductionAllogeneic stem cell transplantation survivors are at a relevant risk of developing chronic GvHD (cGvHD), which importantly affects quality of life and increases morbidity and mortality. Early identification of patients at risk of cGvHD-related morbidity could represent a relevant tool to tailor preventive strategies. The aim of this study was to evaluate the prognostic power of immune reconstitution (IR) at cGvHD onset through an IR-based score.MethodsWe analyzed data from 411 adult patients consecutively transplanted between January 2011 and December 2016 at our Institution: 151 patients developed cGvHD (median follow-up 4 years). A first set of 111 consecutive patients with cGvHD entered the test cohort while an additional consecutive 40 patients represented the validation cohort. A Cox multivariate model for OS (overall survival) in patients with cGvHD of any severity allowed the identification of six variables independently predicting OS and TRM (transplant-related mortality). A formula for a prognostic risk index using the β coefficients derived from the model was designed. Each patient was assigned a score defining three groups of risk (low, intermediate, and high).ResultsOur multivariate model defined the variables independently predicting OS at cGvHD onset: CD4+ >233 cells/mm3, NK <115 cells/mm3, IgA <0.43g/L, IgM <0.45g/L, Karnofsky PS <80%, platelets <100x103/mm3. Low-risk patients were defined as having a score ≤3.09, intermediate-risk patients >3.09 and ≤6.9, and high-risk patients >6.9. By ROC analysis, we identified a cut-off of 6.310 for both TRM and overall mortality.In the training cohort, the 6-year OS and TRM from cGvHD occurrence were 85% (95% CI, 70-92) and 13% (95% CI, 5-25) for low-risk, 64% (95% CI, 44-89) and 30% (95% CI, 15-47) for intermediate-risk, 26% (95% CI, 10-47), and 42% (95% CI, 19-63) for high-risk patients (OS p<0.0001; TRM p = 0.015).The validation cohort confirmed the model with a 6-year OS and TRM of 83% (95% CI, 48-96) and 8% (95% CI, 1-32) for low-risk, 78% (95% CI, 37-94) and 11% (95% CI, 1-41) for intermediate-risk, 37% (95% CI, 17-58), and 63% (95% CI, 36-81) for high-risk patients (OS p = 0.0075; TRM p = 0.0009).ConclusionsIR score at diagnosis of cGvHD predicts GvHD severity and overall survival. IR score may contribute to the risk stratification of patients. If confirmed in a larger and multicenter-based study, IR score could be adopted to identify patients at high risk and modulate cGvHD treatments accordingly in the context of clinical trial.